Avaliação da qualidade de vida e sintomas de depressão, ansiedade e estresse em pacientes com câncer de pele - SILVA, Ricardo Dias (2020)
Introduction: skin neoplasms are the most common type of malignant tumor in humans. Non-melanoma skin cancer is the most common type; malignant melanoma, despite its lower incidence, is an aggressive tumor and is responsible for most deaths caused by skin cancer. It is known that skin cancers have significant impacts on quality of life and can cause psychological changes in the person affected. Thus, it is important to investigate skin cancer patients for the possible repercussions that the disease can cause in all these aspects. Objective: to evaluate the influence of sociodemographic, clinical and work profile variables on quality of life scores and symptoms of depression, anxiety and stress. Methodology: descriptive, correlational, cross-sectional study with a quantitative approach. For data collection, three instruments were used: the first instrument containing sociodemographic, clinical and worker's data; the second was the Quality of Life Questionare “Core” 30 items (QLQ-C30); the third, the Depression, Anxiety and Stress Scale (Portuguese) (DASS-21). The data obtained were entered into the Microsoft® Office Excel® 2007 program and statistical analyzes were performed using the Satistical Pakcage for Social Sciences (SPSS), version 22.0. Distribution was carried out in absolute and relative frequencies for categorical variables and measures of position and variability for quantitative variables; bivariate analysis was performed including Pearson's correlation for quantitative predictors and Spearman's correlation for quantitative and categorical predictors. The simultaneous influence of sociodemographic and clinical predictors on each of the outcomes comprised multiple linear regression analysis. Results: the sample consisted of 74 participants, 67.3% of whom were female; 63% elderly; 94.6% have white skin color and the average education level was 4.93 years of study. The most frequent type of cancer was basal cell carcinoma (71.6%), followed by squamous cell carcinoma (12.1%) and malignant melanoma (10.8%), respectively. The professional activity area most reported by the participants was agriculture (33.8%). The score of the DASS-21 domains showed significant levels of depression, anxiety and stress. Regarding quality of life, no significant results were observed for low quality of life in the dimensions of the QLQ-C30. It was evidenced that the variable education had an impact on the symptoms of depression (β = - 4.165; p = 0.005). The age variable had an impact on the symptoms of depression (β = 0.317; p = < 0.001), anxiety (β = 0.147; p = 0.025) and quality of life (β = - 0.31; p = 0.010), however did not impact stress symptoms. The gender variable influenced anxiety symptoms (β = 1.475; p = 0.737), with women showing a higher index. The presence of chronic diseases impacted quality of life (β = 0.003; p = 0.026). Conclusion: the most common type of skin cancer was basal cell carcinoma, followed by squamous cell carcinoma and malignant melanoma, respectively, with the head and neck as the most common location. Few studies have evaluated the quality of life and psychological characteristics of patients with skin cancer, and there is also a lack of instruments for this purpose. Offering prevention and awareness actions about skin cancer, as well as a deeper knowledge about the general characteristics that involve the individual with skin cancer should be one of the focuses of nursing.